The Impact of Governance Mechanisms on Tax Aggressiveness: Empirical Evidence from Tunisian Context - Boussaidi, Ahmed; Hamed, Mounira Sidhom (Journal of Asian Business Strategy, 2015)
Research on the tax side occupied the stage center during the last decade. Several researchers have attempted to study the different effects of some options such as tax aggressiveness on firms and individuals. Overall, tax aggressiveness affects negatively the longevity of companies but what remains unanswered is by what specific means corporate governance decreases tax aggressiveness activities. In this paper, we examine the effect of some governance mechanisms on corporate tax aggressiveness. The study is based on the analysis of a sample of Tunisian listed firms over the 2006-2012 periods. Our regression results indicate that diversity in gender on corporate board, managerial and concentration ownership has significant effects on firms` tax aggressiveness activities. Board`s diversity and managerial ownership exhibit a positive association with the effective tax rate while increases in concentration ownership tend to affect it negatively. However, findings don`t show any significant effects of corporate board size and external auditor`s profile on the tax aggressiveness.